Molecular profiling of basal cell carcinomas in young patients - Marc Abi Karam; Hampig Raphael Kourie; Nadine Jalkh; Cybel Mehawej; Carole Kesrouani; Fady Gh Haddad; Iman Feghaly; Eliane Chouery; Roland Tomb (BMC, 2021)
Abstract Background Basal cell carcinoma (BCC) represents by far the most common non-melanoma skin cancer (NMSC) in the world with an increasing incidence of 3% to 10% per year, especially in patients under the age of 40. While variants in the sonic Hedgehog and cell cycle regulation pathways account for the majority of BCC cases in adults, the molecular etiology of BCC in young patients is unelucidated yet. This study aims to investigate the molecular profile of BCC in the young population. Methods 28 tumors belonging to 25 Lebanese patients under the age of 40, presenting different stages of BCC and diagnosed at Hôtel Dieu de France-Saint Joseph University Medical Center were included in this study. A selected panel of 150 genes involved in cancer was analyzed by Next Generation Sequencing (NGS) in the 28 included tumors. Results Genetic variants detected in more than 5% of the reads, with a sequencing depth ≥ 50x, were selected. Two hundred and two genetic variants in 48 different genes were detected, with an overall average sequencing depth of 1069x. Among the 28 studied tumors, 18 (64.3%) show variations in the PTCH1 gene, 6 (21.4%) in TP53 and 3 (10.7%) in SMO. Conclusions This is the first study reporting NGS-based analysis of BCC in a cohort of young patients. Our results highlight the involvement of the hedgehog and cell cycle regulation pathways in the genesis of BCC in the general population. The inclusion of a larger cohort of young patients is needed to confirm our findings.